Islet Cell Associated Autoantibodies and C-Peptide Levels in Patients with Diabetes and Symptoms of Gastroparesis - Siraj, Elias S.; Homko, Carol; Wilson, Laura A.; May, Patrick; Rao, Ajay D.; Calles, Jorge; Farrugia, Gianrico; Hasler, William L.; Koch, Kenneth L.; Nguyen, Linda; Snape, William J.; Abell, Thomas L.; et al. (Frontiers in Endocrinology, 2018)
Individuals with diabetes are at increased risk for complications including gastroparesis. Type 1 diabetes mellitus (T1DM) is an autoimmune disorder resulting in decreased beta-cell function. Glutamic acid decarboxylase-65 antibody (GADA) is the most commonly used test to assess autoimmunity while C-peptide level is used to assess beta cell function. Patients with type 2 diabetes mellitus (T2DM), who are GADA positive are labelled latent autoimmune diabetes in adults (LADA). Objective: To characterize patients with T1 and T2DM who have symptoms of gastroparesis using GADA and C-peptide levels and to look for association with the presence of gastroparesis and its symptom severity. Design: 113 T1DM and 90 T2DM patients with symptoms suggestive of gastroparesis were studied. Symptom severity was assessed using Gastroparesis Cardinal Symptom Index (GCSI). Serum samples were analyzed for GADA and C-peptide. Results: Delayed gastric emptying was present in 91 (81%) of T1DM and 60 (67%) of T2DM patients (p=0.04). GADA was present in 13% of T2DM subjects (10% in delayed gastric emptying and 20% in normal gastric emptying [p=0.2]). Gastric retention and GCSI scores were mostly similar in GADA positive and negative T2DM patients. GADA was present in 45% of T1DM subjects (46% in delayed gastric emptying and 41% in normal gastric emptying [p=0.81]). Low C-peptide levels were seen in 79% T1DM patients and 8% T2DM. All 7 T2DM patients with low C-peptide were taking insulin compared to 52% of T2DM with normal C-peptide. Conclusions: GADA was present in 13% while low C-peptide was seen in 8% of our T2DM patients with symptoms of gastroparesis. Neither did correlate with degree of delayed gastric emptying or symptom severity.